An Innovative Method for Rapid Identification and Detection of Vibrio alginolyticus in Different Infection Models - Fu, Kaifei; Li, Jun; Wang, Yuxiao; Liu, Jianfei; Yan, He; Shi, Lei; Zhou, Lijun (Frontiers in Microbiology, 2016)
Vibrio alginolyticus is one of the most common pathogenic marine Vibrio species, and has been found to cause serious seafood-poisoning or fatal extra-intestinal infections in humans, such as necrotizing soft-tissue infections, bacteremia, septic shock and multiple organ failures. Delayed accurate diagnosis and treatment of most Vibrio infections usually result to high mortality rates. The objective of this study was to establish a rapid diagnostic method to detect and identify the presence of V. alginolyticus in different samples, so as to facilitate timely treatment. The widely employed conventional methods for detection of V. alginolyticus include biochemical identification and a variety of PCR methods. The former is of low specificity and time-consuming (2-3 days), while the latter has improved accuracy and processing time. Despite such advancements, these methods are still complicated, time-consuming, expensive, require expertise and advanced laboratory systems, and are not optimal for field use. With the goal of providing a simple and efficient way to detect V. alginolyticus, we established a rapid diagnostic method based on Loop-mediated Isothermal Amplification (LAMP) technology that is feasible to use in both experimental and field environments. Three primer pairs targeting the toxR gene of V. alginolyticus were designed, and amplification was carried out in an ESE tube scanner and Real-Time PCR device. We successfully identified 93 V. alginolyticus strains from a total of 105 different bacterial isolates and confirmed their identity by 16s rDNA sequencing. We also applied this method on infected mouse blood and contaminated scallop samples, and accurate results were both easily and rapidly (20-60min) obtained. Therefore, the RT-LAMP assay we developed can be conveniently used to detect the presence of V. alginolyticus in different samples. Furthermore, this method will also fulfill the gap for real-time screening of V. alginolyticus infections especially while on field. Keywords: Vibrio alginolyticus; toxR gene; Real-Time LAMP; 16s rDNA sequencing; rapid detection